Studies on bacterial speck of tomatoes caused by Pseudomonas syringae pv tomato : a thesis presented in fulfilment of a Masterate of Science by thesis only at Massey University - Pyke, Nicholas Brian (Massey University, 1980)
The taxonomy of the causal agent of bacterial speck of tomatoes is discussed and the trinomial Pseudomonas syringae pathovar tomato (Okabe) Young, Dye and Wilkie is adopted. A vacuum infiltration method of artificially inoculating seed was used and P.syringae pv tomato was detected in both artificially and naturally infested seed using sensitive enrichment culture techniques. The pathogen can remain viable between seed harvest and sowing in association with seed but seed-plant transfer was only occasionally demonstrated. The acid seed extraction method and other germicidal seed treatments were evaluated for their effect on the seedborne pathogen. Streptomycin sulphate as a slurry treatment (2.5g a.i./Kg of seed) just prior to seed sowing was the only totally effective seed treatment tested. The potential for survival in infected crop debris, soil and on alternative hosts was shown. However, the pathogen was not isolated from weeds in infected tomato crops and no conclusive evidence of systemic infection was found.
Page 42 is missing from the original copy.
Keywords: Pseudomonas syringae; Tomatoes -- Diseases and pests